Jurisdição constitucional e democracia: uma análise fenomenológica de manifestações decisórias em sede de controle difuso de constitucionalidade - Leiria, Maria Lucia Luz (Universidade do Vale do Rio do Sinos, 2007)
The present thesis aims to appreciate highly the principle disposed on the article 97 of the Brazilian Constitution by which the absolute majority number of plenary members (Full Bench) is requested in order to judge the questions related to the control of the constitutionality, as well as the necessity of the maintenance of the diffused control of the constitutionality, to conclude that the constitutional jurisdiction is necessary and indispensable for supporting the democracy. This study takes into consideration the decisions referring to the diffused control of the constitutionality over laws and normative acts given by the Federal Regional Court of the 4th Circuit with jurisdiction over the states of Rio Grande do Sul, Santa Catarina and Paraná, and those pronounced by the Superior Court of Justice. It is possible to apprehend that the horizontality of the diffused control works as an indispensable element to maintain the balance among the Republic powers, permiting the provocation of the constitutional j
Keywords: controle difuso; democracia; reserva de plenário; jurisdição constitucional; democracy; diffused control; full bench; constitutional jurisdiction; Ciências Sociais Aplicadas